AMAZONIAN VÁRZEA FORESTS: ADAPTIVE STRATEGIES OF TREES AS TOOLS FOR FOREST MANAGEMENT - Parolin, Pia (2016)
Amazonian várzea forests are characterized by a high diversity of species and adaptations against extended flooding. Waterlogging and submergence can last up to 210 days per year, with a water column of up to 6-7 m. The present paper gives an insight into the current knowledge of morpho-anatomical, phenological and physiological responses to flooding in várzea trees, into patterns of regeneration and seedling recruitment, and into differences found along the flooding gradient, and between populations of selected species. This knowledge may serve as a basic tool for forest management. The high selective logging already caused a substitution of timber species, with high damages in the remaining stands, calling for rigorous management plans. Since the regular inundation induces the formation of annual rings, and tree growth responds to the prolonged vegetation period with significantly wider ring widths in El Niño years as compared to neutral years, tree ring analysis can be used also for the development of models to predict tree growth and to determine minimum logging diameters and cutting cycles for timber species. Keywords: Amazonia, tree ecophysiology, establishment, environmental gradients, productivity, speciation, tree-ring analysis, El Niño.